Mobile Biomonitoring of Atmospheric Pollution: A New Perspective for the Moss-Bag Approach - Maria Cristina Sorrentino (MDPI AG, 2021)
In this work the potential of moving moss-bags, fixed to bicycles, to intercept particulate matter (PM) and linked metal(loid)s was tested for the first time. Seven volunteers carried three moss-bags for fifty days while commuting by bicycle in the urban area of Antwerp, Belgium. Moreover, one bike, equipped with mobile PM samplers, travelled along four routes: urban, industrial, green route and the total path, carrying three moss-bags at each route. The saturation isothermal remanent magnetization (SIRM) signal and chemical composition (assessed by HR-ICP-MS) of the moss samples indicated that the industrial route was the most polluted. Element fluxes (i.e., the ratio between element daily uptake and the specific leaf area) could discriminate among land uses; particularly, they were significantly higher in the industrial route for Ag, As, Cd and Pb; significantly lowest in the green route for As and Pb; and comparable for all accumulated elements along most urban routes. A comparison with a previous experiment carried out in the same study area using similar moss-bags at static exposure points, showed that the element fluxes were significantly higher in the mobile system. Finally, PM2.5 and PM10 masses measured along the four routes were consistent with element fluxes.